Retail travel agent Service recovery toward customer satisfaction / Nur Adlinna Mohamed , Nur Syafikah Wan Jusoh and Mazlina Mahdzar. - Mohamed, Nur Adlinna; Wan Jusoh, Nur Syafikah; Mahdzar, Mazlina (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2017)
Retail travel agents have focused on providing high quality of service in ensuring they are not far behind in the competition against rival. However the low quality of services is the expected cause of travel agency service failure. Therefore, service recovery has become an important tool to acquire customers' satisfaction towards the travel agency services. This study aimed to examine how customers perceived the service recovery behaviours they have received previously after they have encountered with service failure. Hence, the objectives of this study was designed and measured with fairness theory. This study focused on the relationship between perceived fairness and customer satisfaction in service recovery from a travel agency. Research instrument was developed and data was collected from customers who previously used travel agency in Malaysia for their vacation. The findings showed that distributive fairness and interactional fairness are positively connected with customer satisfaction.